Constitution of self-efficacy in the early career of physical education teachers - Filho, Roraima A. Costa [UNESP]; Iaochite, Roberto T. [UNESP] (My University, 2018)
Problem statement: Teaching self-efficacy is built from teacher's interpretations about and also from the personal values that he attributes to the information selected from the environment. Despite research has investigated the contributions of the sources of self-efficacy, little is known about which experiences are selected and weighted by Physical Education beginning teachers to compose teacher' self-efficacy. Purpose: This study aimed to identify, describe and analyze the learning experiences to teach that beginning Physical Education teachers rely on to judge their self-efficacy to teach. Approach: The data were collected through semi-structured interviews with five Physical Education beginning teachers and qualitatively analyzed with the support of NVivo software. Results: Results indicate the prevalence of practical experiences (enactive mastery experience) during teacher education, especially linked to supervised practicum, observational learning experiences (vicarious experience), and teacher guidance (social persuasion) during ongoing education were also significant information for the self-efficacy judgments. Conclusion: special attention can be given to the processes of the supervised practicum programs and situations which involve direct teaching practices during the undergraduate courses and in-service programs.
Keywords: Beginning teacher; Physical education; Self-efficacy; Sources of self-efficacy